2017
DOI: 10.1007/s13577-017-0180-z
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of miR-23a inhibits high glucose-induced EMT and renal fibrogenesis by up-regulation of SnoN

Abstract: It has been reported that transforming growth factor-β1 (TGF-β1) signaling plays an important role in the development of diabetic nephropathy (DN). The nuclear transcription co-repressor Ski-related novel protein N (SnoN) is a critical negative regulator of TGF-β1/Smad signal pathway, involving in tubule epithelial-mesenchymal transition (EMT), extracellular matrix (ECM) accumulation, and tubulointerstitial fibrosis. In this study, we focused on miR-23a as a regulator of SnoN. Our purpose is to study the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…miR-let7b and miR-let7d and fibrogenesis are downregulated by TGF-β1 in NRK52E cells, and miR-let7c is also downregulated in HK2 cells under fibrotic conditions [91]. miR-let7b expression is consistent in different animal model of renal fibrosis [11,92], and decreases in miR-let7a-5p have been observed in UUO model mice, contributing to the excessive deposition of collagen and tissue fibrosis in the kidney [46].…”
Section: Mir-let7mentioning
confidence: 84%
See 1 more Smart Citation
“…miR-let7b and miR-let7d and fibrogenesis are downregulated by TGF-β1 in NRK52E cells, and miR-let7c is also downregulated in HK2 cells under fibrotic conditions [91]. miR-let7b expression is consistent in different animal model of renal fibrosis [11,92], and decreases in miR-let7a-5p have been observed in UUO model mice, contributing to the excessive deposition of collagen and tissue fibrosis in the kidney [46].…”
Section: Mir-let7mentioning
confidence: 84%
“…However, another isomiR of mir-23, miR-23a, seems to have the opposite expression trend. miR-23a was recently found to be upregulated in renal tissues of diabetic patients and HK2 cells treated with HG [46].…”
Section: Mir-23mentioning
confidence: 99%
“…Liu et al reported that miR-130a-5p prevented angiotensin II-induced podocyte apoptosis by modulating phospholipase A2 receptor (PLA2R) [68]. In spite of these trophic effects, miR-130a-3p has been reported to target SnoN, thereby promoting renal fibrosis via TGF-β1/Smad pathway, similar to miR-23a [69]. Further analysis is still required to conclude the potential effects of miR-130a in renal diseases.…”
Section: Versatile Msc-evs-derived Mirnas Modulate Renal Injury and Hmentioning
confidence: 99%
“…A high level of miR-23a was also observed in diabetic patients and HG-cultured TECs. It directly targets the nuclear transcription co-repressor Ski-related novel protein N (SnoN) (Tan et al, 2006), a crucial negative regulator to TGFβ/Smad3-mediated signaling pathway, to induce fibrosis in DKD (Xu et al, 2018a). Sirtuin 1 (SIRT1) expression in the nucleus and the cytoplasm has also been shown as a renoprotective regulator by inhibiting TGF-β/Smad-induced fibrosis and downstream hypoxia-inducible factor-1α (HIF-1α).…”
Section: Non-smad-dependent Mirnas In Dkdmentioning
confidence: 99%